Comparison of Wind Potential of Ormara and Jiwani (Balochistan), Pakistan - Tariq Jamil; G.S. Akram Ali Shah (Journal of Basic & Applied Sciences, 2016)
This paper presents comparison of wind potential of Ormara and Jiwani and evaluation of Weilbull distribution function for two coastal areas of Balochistan. Ten years data (1998-2007) of wind speed have been obtained from Pakistan Meteorological | department (PMD) of Karachi, Pakistan. The analysis of wind data is carried out and fitted by Weibull function. The two parameters of the distribution are also evaluated. Monthly mean wind speed of two coastal locations (Ormara and Jiwan) was also predicted.